The critical role of evidence-based policy & practice : enhancing participation in the Information Society and citizen-centric e-government in the Caribbean - Bertin, Cletus Kennedy (CARICAD [St. Michael]BB, 2006)
Argues that in order for e-citizenship to have an empowering and developmental impact on all sectors of society, the process of citizen participation must begin from the formulation of ICT policies and strategies, and not simply at the end stage, characterized by online interaction mediated by computer and Internet-based techologies.